Economic impact of agricultural micro-enterprises in the Arica desert: an approach to business assistance provided by the Sercotec Arica Business Center of Chile - Novoa, Rodrigo Ignacio Barra (The journal of contemporary issues in business and government, 2021)
The article analyses under a descriptive and case study methodology the first economic impact results of the Small Business Development Center of Arica, a program financed by the Technical Cooperation Service (SERCOTEC). The preliminary conclusion of the article suggests that the first economic impact results show that the assisted enterprises in the Arica and Parinacota Region, especially in the agricultural segment exhibit certain similarities in most areas of business assistance that explain their positive performance in terms of increased sales. It is also argued that the sustained capacity to identify new market opportunities and make efficient use of their productive resources - due to the local soil and climate conditions in the middle of the Atacama Desert - induce them to innovate permanently, stimulating the insertion of their products in more profitable markets, a fact that also explains their better economic performance.